STUDENTS' AND TEACHER'S PERSPECTIVES TOWARD THE USE OF "THINKQUEST" IN INDONESIAN CONTEX :A Research of Language Learning Media with 1st Graders of an SMAN in Bandung - Ihsan Solihin, - (2012)
This research is a descriptive study which investigated both students' and teachers' perspectives towards the use of ThinkQuest as an alternative learning medium. Besides, this study explores the students' and the teacher's difficulties in using ThinkQuest. This research involved a class and an English teacher from a state senior high school in Bandung. This research employed both qualitative and quantitative approaches to answer the research questions. Interview and questionnaire were undertaken to obtain the data. Data analysis in this research was undertaken through comparing the obtained data to related theories including the related theories of ThinkQuest and the problems faced by students and teacher during the implementation of ThinkQuest. The findings indicate that both the students and the teacher did not seem to have good understanding of ThinkQuest since it was a new medium in teaching and learning context in Indonesia. Nevertheless, both students and teacher were aware that ThinkQuest could improve students' motivation to do individual and group learning as well as improving students' creativity in learning activity. In addition, there are two difficulties faced by the students and teacher in using ThinkQuest: lack of computer hardware and internet connection and lack of understanding to use ThinkQuest. As the result, the students and the teacher perceived that ThinkQuest can be considered as one of effective learning media.